Investigating of Students' Metaphorical Thinking in Solving Algebra Problems - Walfurqan, Walfurqan (Universitas Negeri Surabaya, 2020)
This study aims to describe the students' metaphorical thinking in solving algebraic problems especially in view of differences in their mathematical abilities. Metaphorical in this study refers to metaphorical thinking with CREATE criteria. This research uses descriptive research with a qualitative thinking approach. The subjects of this study consisted of three VII grade students of Al-Falah Surabaya Middle School with one subject from each category of high, medium and low mathematical abilities. Data collection is done by written assignments and interviews. To test the credibility of the data is done by time triangulation. At different times the tasks and interviews are given with problems that are equivalent to the previous tasks. The results showed that students with high mathematical abilities can reveal all CREATE criteria, students with moderate abilities can already check by writing down the steps in making models, operating and completing them. In addition, students did not reveal the criteria for transform, when in fact he had done it in the previous stage. Furthermore, students with low ability only re-read metaphors and their compatibility with the problem. These students did not reveal the criteria to relate, explore, analyze and experience. Keywords: Metaphorical Thinking, Algebra Problem Solving, and Mathematical Ability.